Global PM2.5 exposures and inequalities - Chenyang Xu; Kaiming Xia; Zhehan Huang; John J. Qu; Ashbindu Singh; Ziqian Ye; Qingquan Li; Jizhe Xia (npj Climate and Atmospheric Science)
Abstract Inequalities in exposure to PM2.5 reflect disproportionate distribution of health risks across populations. This study assesses global PM2.5 exposure inequalities and associated trends since 2000. Results show that 118 countries reduced intra-country inequalities, but global disparities intensified due to widening gaps between developing and developed regions. By identifying pathways and country-specific contributions to global inequalities, we show that environmental policy shifts in major economies can rapidly reshape global inequality patterns.